Standing Up for Culturally Competent Care in Portugal: The Experience of a “Health in Equality” Online Training Program on Individual and Cultural Diversity - Violeta Alarcão; Sandra Roberto; Thais França; Carla Moleiro (Societies, 2022)
Health professionals play an essential role in the protection and promotion of health rights without distinction of sex, sexual orientation, gender identity and expression, ethnicity/race, nationality and migration status, age, functional diversity, or any other individual and/or cultural positions. With the growing diversity of patient populations, health professionals must be able to identify and be responsive to individual and cultural diversity, ensuring equity in access to high-quality individually-centered care. For this, it is fundamental to promote training in cultural competence, understood as responsivity and the ability to work the valorization of multiple and intersectional identities throughout life. The paper aims to describe the experience of the implementation of the program “Health in Equality”, aimed at training the primary healthcare workforce in Portugal, which was based on Sue and Sue’s (2008) three-dimensional model of multicultural skills, which champions cultural best practices in an intersectional perspective. Based on the trainees’ and trainers’ evaluation of four completed editions developed online between March and July 2021, this study discusses ways to improve the impact of the training program and amplify the number of leaders and role models for other health care providers towards culturally competent healthcare systems and organizations.